1983
DOI: 10.3109/17453678308996587
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Severe Proximal Humeral Fractures

Abstract: Results after the operative treatment of 41 severe proximal fractures of the humerus are reported. The fractures were classified according to Neer (1970a). The aim of treatment was accurate reduction and stable fixation of the fracture with screws or with screws and a plate. When scored according to Neer's (1970a) functional assessment, results in the 31 patients re-examined more than 1 year postoperatively were excellent or satisfactory in 23 patients. Results were excellent or satisfactory in 14/15 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1
5

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(91 citation statements)
references
References 5 publications
8
77
1
5
Order By: Relevance
“…26 Paavolainen et al studied 41 patients in their series and they concluded that displaced fractures of the proximal humerus treated with open reduction and internal fixation gave good results in 74% of cases. 27 In our study based on Neer's functional scoring system, 18 patients had an excellent result while satisfactory results were seen in 10 patients and 2 patients had a poor result which was comparable with that of other studies. The results of surgical management were better in Neer's 2 part fractures as compared to 3 and 4 part fractures.…”
supporting
confidence: 79%
“…26 Paavolainen et al studied 41 patients in their series and they concluded that displaced fractures of the proximal humerus treated with open reduction and internal fixation gave good results in 74% of cases. 27 In our study based on Neer's functional scoring system, 18 patients had an excellent result while satisfactory results were seen in 10 patients and 2 patients had a poor result which was comparable with that of other studies. The results of surgical management were better in Neer's 2 part fractures as compared to 3 and 4 part fractures.…”
supporting
confidence: 79%
“…At final followup, the average humeral neck-shaft angle was 130.4° (range, 111°−139°). When the neck-shaft angles were classified based on the method by Paavolainen et al, 13) 54 patients had a score of 'excellent', 2 patients 'good', and none 'poor'. The postoperative humeral neck-shaft angle was on average 6.2° (range, 1°−19°) different relative to the unaffected contralateral shoulder.…”
Section: Resultsmentioning
confidence: 99%
“…The neck-shaft angle was graded radiographically according to Paavolainen et al's method as "good" (121°−140°), "fair" (100°−120°), or "poor" (less than 100°). 13) Further, the accuracy of anatomical reduction was assessed by confirming whether the medial side of the fracture achieved anatomical reduction. The degree of post-operative loss of reduction was measured by comparing the humeral neck-shaft angles and the humeral head height at immediate postoperative and at final follow-up on anteroposterior radiographs (Fig.…”
Section: Assessment Of Clinical Outcomesmentioning
confidence: 99%
“…The results reported by Neer (1970b) have not been convincingly confirmed by others. Using the Neer assessment key, closed, as well as open, reduction and internal fixation seems to yield 50-60 per cent reported by Paavolainen et al (1983) and Stableforth (1984).…”
Section: Discussionmentioning
confidence: 99%